Short-term power output forecasting for large multi-megawatt photovoltaic systems with an aggregated low-level forecasting methodology - Du Plessis, Armand (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.